Decision support methods and applications in the upstream oil and gas sector - Shafiee, Mahmood; Animah, Isaac; Alkali, Babakalli; Baglee, David (Elsevier, 2018)
Decision-making support (DMS) methods are widely used for technical, economic, social and environmental assessments within different energy sectors, including upstream oil and gas, refining and distribution, petrochemical, power generation, nuclear power, solar, biofuels, and wind. The main aim of this paper is to present a comprehensive literature review and classification framework for the latest scholarly research on the application of DMS methods in the upstream oil and gas industry. To achieve this aim, a systematic review is conducted on the current state-of-the-art and future perspectives of various DMS methods applied to different upstream operations (such as exploration, development and production) which take place prior to shipping of crude oil and natural gas to the refineries for processing. Journal and conference proceeding sources that contain literature on the subject are identified, and based on a set of inclusion criteria the related papers are selected and reviewed carefully. A framework is then proposed to classify the literature according to the year and source of publications, type of fossil fuel sources, stages of oil and gas field lifecycle, data collection techniques, decision-making methods, and geographical distribution and location of case studies. The proposed literature classification and content analysis can help upstream oil and gas industry stakeholders such as field owners, asset managers, service providers, policy makers, environmentalist, financial analyst, and regulatory agencies to gain better insight about their business activities with well-informed decision-making processes.
Keywords: Decision-making; Asset risk management; Decision support system (DSS); Upstream oil and gas; Uncertainty